From a Public Space to a Shopping Mall: The Case of City Square in Bursa, Turkey - Polat, Sibel; DOSTOĞLU, NESLİHAN (My University, 2011)
In recent years, many new projects have been prepared for neglected public spaces which have lost their functions in different cities of Turkey, either by means of private commissions or competitions. However, this process has generally resulted either in the complete disappearance of public spaces or the transformation of public spaces to transit areas or more controlled spaces like shopping malls. The Central Garage, which was constructed in 1961 as the largest garage of the Balkans and which was used for thirty five years as the terminal of Bursa is an interesting example for this subject. After the Central Garage lost its function as a terminal, it was abandoned, and experienced physical and social dilapidation for a long time, and was finally transformed into a shopping mall. This paper aims to evaluate the process during which the Central Garage was transformed from a public space to a shopping mall in Bursa.
Keywords: Public Sphere; Public Space; Physical and Social Dilapidation; Urban Regeneration; Central Garage; City Square; Bursa